Penguatan Moderasi Beragama Berbasis Sistem Kekerabatan Polong Renten dalam Pengabdian Kepada Masyarakat di Kabupaten Lombok Utara - John Abraham Ziswan Suryosumunar; Srirahayu Puspawati; Wiranto Tasijawa (IAHN Gde Pudja Mataram, 2023)
This article was arranged by the author to describe the implementation of community service program carried out by the author and the community service team of the Hindu Philosophy department, Institut Agama Hindu Negeri Gde Pudja Mataram in Sangaran hamlet, Selelos, North Lombok. Community service program carried out by the author consist of counseling with the theme Strengthening Religious Moderation Based on the Polong Renten Kinship System which is carried out by lecture and Q&A method, then also the implementation of mutual cooperation in the form of community service with the Sangaran people in the Banjar Dana Laksana temple environment as an affective approach. From the discussion in this article, it can be concluded that: First, the counseling conducted by the author as a speaker in community service program in the Sangaran hamlet provides a paradigm foundation related to the compatibility between the principle of religious moderation and the polong renten kinship system, in this case the community is invited to understand the common ground of various religious and cultural teachings and understand what factors need to be abandoned to avoid conflict. Second, mutual cooperation activities with community service around the Banjar Dana Laksana temple provide a stimulus for the community to animate universal solidarity which is the basis of the polong renten kinship system and it’s also able to strengthen the principle of religious moderation in daily life.